2016
DOI: 10.1589/jpts.28.3279
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of ambulation patterns and isokinetic muscle strength for the application of rehabilitation exercise in patients with patellofemoral pain syndrome

Abstract: [Purpose] The aim of this study was to evaluate the differences in the ambulation patterns and knee joint performance between people with and without patellofemoral pain. The present study also aimed to utilize these results as a basis for the development of pain-alleviating and performance-improving treatment programs. [Subjects and Methods] Subjects consisted of 32 adult females diagnosed with patellofemoral pain syndrome and 25 adult females without patellofemoral pain (controls). Contact ratio patterns dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
2
3
0
Order By: Relevance
“…Moderate to large knee strength deficits identified in this study are consistent with a number of previous studies in women with PFP (9-30%) (12,13,16,40). Other studies evaluating dynamic knee strength have reported greater deficits in women with PFP (37-71%) (20,53) compared with results of this study (12-21%). This inconsistency may be explained by the lack of torque normalization (20,53).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Moderate to large knee strength deficits identified in this study are consistent with a number of previous studies in women with PFP (9-30%) (12,13,16,40). Other studies evaluating dynamic knee strength have reported greater deficits in women with PFP (37-71%) (20,53) compared with results of this study (12-21%). This inconsistency may be explained by the lack of torque normalization (20,53).…”
Section: Discussionsupporting
confidence: 90%
“…Other studies evaluating dynamic knee strength have reported greater deficits in women with PFP (37–71%) (20,53) compared with results of this study (12–21%). This inconsistency may be explained by the lack of torque normalization (20,53). Nevertheless, results from this study, along with other reported findings (12,13,16,20,40,53), highlight the potential importance of addressing knee muscle strength during rehabilitation of PFP (21).…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…4 Proposed by clinical research to explore professional rehabilitation method application in the rehabilitation after knee cruciate ligament reconstruction, establish knee anterior cruciate ligament reconstruction, postoperative rehabilitation training standard and specification, the maximum recovery in patients with motor function, so as to solve the knee anterior cruciate ligament injury rehabilitation in prominent and urgent problem, provide a reference basis for the postoperative rehabilitation treatment. 5…”
Section: Introductionmentioning
confidence: 99%